Challenges with bioaugmentation and field-scale application of bioremediation processes for petroleum-contaminated sites: a review - Koolivand, Ali; Coulon, Frederic; Ball, Andrew S.; Ismail, Nur Izzati; Khudur, Leadin S.; ParsiMehr, Mohamad; Gao, Guanyue; Godini, Kazem (Springer, 2024)
Bioremediation is a promising method for cleaning up sites contaminated with petroleum hydrocarbons (PHs), with bioaugmentation being a common strategy that involves the use of microbial consortia to treat these sites. However, using a single bacterium is not effective in treating PHC contamination due to the range of compounds present. The use of different strains as a consortium can improve treatment, but bioaugmentation often fails due to various factors, especially in large-scale applications. The number and survival of introduced microorganisms are critical during bioremediation, and immobilization by using carrier materials such as biochar can protect added microorganisms from adverse impacts. Advanced composting methods can also be effective in treating petroleum-polluted sites in commercial-scale applications. By adjusting environmental factors and adding compost, native microorganisms can be biostimulated. This review aims to critically analyze the challenges associated with bioaugmentation and field-scale applications of bioremediation for petroleum-contaminated sites, specifically identifying key variables that impact the success of bioremediation efforts and evaluating the effectiveness of different bioremediation strategies in field conditions. The review addresses the primary factors contributing to the failure of bioaugmentation in large-scale applications, how the survival and activity of introduced microbial consortia can be enhanced in contaminated environments, and the most effective strategies for field-scale bioremediation of petroleum-contaminated sites. The strategies discussed are evaluated based on their ability to enhance microbial survival, their practicality in large-scale applications, their environmental impact, and their overall effectiveness in reducing PHC levels. By providing a comprehensive analysis of these aspects, this review aims to offer insights into optimizing bioremediation processes for field-scale applications.
Keywords: 3107 Microbiology; 31 Biological Sciences; Petroleum hydrocarbons; Bioaugmentation challenges; Biotic and abiotic factors; Biochar immobilization; Advanced composting methods